Nonlinear stability of thin FGM annular spherical segment in thermal environment - Anh, Vu Thi Thuy; Bich, Dao Huy; Duc, Nguyen Dinh (Vietnam Journal of Mechanics, 2015)
The nonlinear stability of functionally graded material (FGM) annular spherical segment resting on elastic foundations in thermal environment is studied analytically. Based on the classical thin shell theory, the governing equations are derived. Approximate solutions are assumed to satisfy the simply supported boundary condition and Galerkin method is applied to obtain closed-form relations of bifurcation type of buckling and post-buckling loads. In the present research an analysis is carried out to show the effects of material, geometrical properties, elastic foundations and combination of external pressure and temperature on the nonlinear stability of the shell.